1987
DOI: 10.1128/jb.169.3.1338-1340.1987
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence in Bacillus megaterium of uridine 5'-diphospho-N-acetylgalactosamine and uridine 5'-diphosphogalactosamine, intermediates in the biosynthesis of galactosamine-6-phosphate polymer

Abstract: We isolated two galactosamine derivatives from Bacillus megaterium sporulating cells by lectin affinity chromatography followed by DEAE-Sephadex A-25 chromatography. From chemical analyses and measurements of these compounds, it was determined that one was uridine 5'-diphospho-N-acetylgalactosamine and that the other was uridine 5'-diphosphogalactosamine. They appeared in the middle stage of sporulation and disappeared during the period when galactosamine-6-phosphate is deposited on the forespore surface. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Finally, a number of earlier studies speculate that the exosporium of B. megaterium QM B1551 spores contains a galactosamine-6-phosphate polymer skeleton that confers rigidity to the structure (14,25,32). A number of genes that may have a role in the synthesis of such a polymer, including BMQ_pBM60014 and BMQ_pBM60015, are carried, typically in clusters, on plasmid pBM600.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a number of earlier studies speculate that the exosporium of B. megaterium QM B1551 spores contains a galactosamine-6-phosphate polymer skeleton that confers rigidity to the structure (14,25,32). A number of genes that may have a role in the synthesis of such a polymer, including BMQ_pBM60014 and BMQ_pBM60015, are carried, typically in clusters, on plasmid pBM600.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that galactosamine-6-phosphate polymer begins to be deposited on the forespore from t9 (17) and may be responsible for the surface hydrophobicity of the spore (22). In this study, it was indicated that this sugar polymer does not participate in the deposition of P36 and P22, but may play the role in protecting these OL proteins against the releasing factor after deposition, because loss of these proteins was not observed in the mature spore and the forespore at tio of the wildtype strain where the sugar polymer had been deposited.…”
Section: Discussionmentioning
confidence: 99%